Evaluation of Free Online Machine Translations for Croatian-English and English-Croatian Language Pairs - Seljan, Sanja (Array, 2011)
This paper presents a study on the evaluation of texts from four domains (city description, law, football, monitors) translated from Croatian into English by four free online translation services (Google Translate, Stars21, InterTran and Translation Guide) and texts translated from English into Croatian by Google Translate. The aim of the paper is to conduct a machine translation evaluation of free translation services and to measure inter-rater agreement and the influence of error types on the criteria of fluency and adequacy. The evaluation is performed by students and the results are analyzed by Fleiss kappa and Pearson’s correlation.